Tindak Pidana Pembunuhan Berencana yang Memiliki Indikasi Schizophrenia - Alief Raihan; Setiyono Setiyono; Hatarto Pakpahan (University of Merdeka Malang, 2022)
Case of Murder committed by Perpetrator Sugeng Santoso in case Number 535/Pid.B/2019/PN. Mlg is a criminal case of murder followed by tattooing and mutilating the victim. Previously, the perpetrator was often in and out of the Mental Hospital and according to the testimony of the witness, the Defendant was an insane person, suffering from a mental disorder and symptoms of schizophrenia. This study aims to find out and analyze the considerations in the District Court Decision which states the defendant committed a criminal act of premeditated murder and analyze the criminal conviction by the judge in case Number 535/Pid.B/2019/PN. Mlg is appropriate when viewed from the purpose of punishment and by using normative legal research. The basis for the judge's legal considerations in proving the elements of a criminal act of premeditated murder by a perpetrator with a history of mental disorder/schizophrenia in decision number 535/Pid.B/2019/PN. Please, by using the statements of witnesses, expert statements, evidence of the Visum Et Repertum, and the defendant's statements, there has been a correspondence between one and the other where the Defendant Sugeng Santoso still has to be held accountable for his actions for the crime of premeditated murder even though the Defendant is suspected of having a schizophrenic disorder. and was treated in a mental hospital. The judge's legal considerations in imposing a crime against the perpetrator of the crime of premeditated murder with a history of mental disorders/schizophrenia in decision number 535/Pid.B/2019/PN. Mlg in the form of a prison sentence of twenty years is appropriate and fulfills the principle of justice for both the defendant and the victim with the consideration that the defendant has the capacity to be responsible based on the prevailing laws and regulations and based on jurisprudence by considering aggravating circumstances and mitigating circumstances based on Article 197 of the Criminal Procedure Code.